PROFUNDIDADE DE SEMEADURA E DEFICIÊNCIA HÍDRICA AFETAM O DESENVOLVIMENTO DO SORGO (Sorghum bicolor L.) - TENÒRIO NETO, Joaquim; MARTINS, Murilo Battistuzzi; DO NASCIMENTO, Ana Carolina Vital; SILVA, Alana Rocha; ARAÚJO, Adrielly Patricia Batista; VETRUVE, Italo Ferreira (ANAIS DO ENIC, 2025)
-